A construção contraditória do discurso identitário no cancioneiro de Soledad Pastorutti no contexto do folclore argentino - Souza, Nathan Bastos de (2017)
This dissertation aims to investigate the presence of contradiction indexes that materialize themselves in Soledad Pastorutti’s identity discourse, within her folk music body of work (corpus), while pointing toward otherness, through an analysis of the dialogic relations between folk corpora, their context of production, the music industry narrative, a few biographical reports, and a few songs. This dissertation’s theoretical approach is taken from bakhtinian theory and focuses mainly on the subjects of analysis of contradiction, ambivalence, and bivocality. The methodology of the analysis is based on the notion of text comparison and takes ideological signs as the materialization of social value attribution in language. The results confirm the thesis that the identity discourse in Soledad Pastorutti’s folk music corpus is built under the auspices of self-contradiction, given that within the limits of a single linguistic unit – sometimes a word, sometimes a whole sentence – two voices can be heard: a first one, more apparent, which defends the identity discourse while attacking the “other”, and a second one, less apparent, which shows how far identity constitutes itself in relation to otherness. In other words, the resistance to otherness is ambivalent, bivocal, and contradictory, inasmuch as the discourse that attacks others constitutes itself in difference. It is an identity discourse founded on the contradiction of repealing what is actually constitutive.